y=(4x-18)-(-18+5X)

Simple and best practice solution for y=(4x-18)-(-18+5X) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=(4x-18)-(-18+5X) equation:


Simplifying
y = (4x + -18) + -1(-18 + 5X)

Reorder the terms:
y = (-18 + 4x) + -1(-18 + 5X)

Remove parenthesis around (-18 + 4x)
y = -18 + 4x + -1(-18 + 5X)
y = -18 + 4x + (-18 * -1 + 5X * -1)
y = -18 + 4x + (18 + -5X)

Reorder the terms:
y = -18 + 18 + -5X + 4x

Combine like terms: -18 + 18 = 0
y = 0 + -5X + 4x
y = -5X + 4x

Solving
y = -5X + 4x

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = -5X + 4x

See similar equations:

| 3(4x+8)=80 | | -1.9r-9.3=15 | | 8n(6n+5)=7 | | 6.7=8.5-0.2x | | 4k+3v-10v-2k= | | 5+h=-3 | | 9y+270=10x | | 2(y+3)=4(y+5) | | -20g-20=-18g+16 | | 2x-1+7x=5 | | -3s+16=12s-14-18s | | 2x+5x-9=47 | | 3-2e=8-x | | 8x+3y+7y-2x= | | 21.64=4g+3.56 | | -18-19v=-16v | | -4x-3=12x-35 | | -8(x-7)=-48 | | -4u-7=4+7u | | 8+b=4 | | 6+7(x-7)=-5 | | -9(x-1)=-63 | | 7j-2=6j | | 29+7x=-4(7-7x)-6 | | 3=w*3-16 | | 7+6p=10p-9 | | -4(r+7)=-45 | | 11.72*x=16.6424 | | 6-k+2k=10-3k | | -q+9=2q | | 29+7x=-4(7-7x) | | 5x+11y+3=0 |

Equations solver categories